PROMOTING ECOLOGICAL AWARENESS IN METAL GEAR SOLID V: SOCIAL SEMIOTIC APPROACH - Kurniawan, Muhammad Hafiz; Gunawan, Wawan; Sudana, Dadang (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Video game is a new media of telling stories to young people and adults and it is no longer seen as gameplay only but gameplay with story. Metal Gear Solid V: The Phantom Pain took Cold War as the main story background tells the story differently. The game system of this video game offers freedom to players to interact with anything during the gameplay, but this freedom has consequences. Applying social semiotic approach, this paper aims to identify how appraisal theory and narrative representation can be used to promote ecological awareness. After observing, collecting and viewing, transcribing and analyzing multimodal data, the researchers find that killing non-playable characters in form of human and animals and even enemy will reduce the score which is important in developing the playable characters’ weapons and equipment. Adopting the theory from Martin White in appraisal theory and Kress and van Leewuen, Caple in narrative representation, this paper also finds that appraisal theory is used to guide the players to play in ethical way such as using non-lethal weaponry, capturing wild animals to protect them from war, and collecting medical plants as needed only, besides, the enemy soldiers can be hired and give beneficial results to the players when they are used to play. In narrative representation, the freedom of choices is designed to make ethical play more plausible.